Fighting Back Against Achievement Culture: Cheating as an Act of Rebellion in a High-Pressure Secondary School. Issue 2 (17th February 2017) - Redding, Alexis Brooke
Abstract : This article argues that document analysis can add a more nuanced understanding of student ethical reasoning and enhance current approaches to cheating research. To demonstrate the benefits of this approach, I examine the cheating epidemic at Stuyvesant High School through editorials in their school newspaper. Stuyvesant is known for academically talented students focused on elite college admission. My findings suggest that the influence of achievement culture on cheating is more complex than what was captured by the school's internal cheating survey or in traditional cheating research. Further, contrary to existing expectations, students do not collaborate purely to boost their own academic performance. In a system they define as unfair and rigged, they collaborate even when it puts them at an academic disadvantage. The finding that there is a sense of communal rebellion against their achievement-oriented context demonstrates the efficacy of document analysis as a complementary approach for understanding student cheating.